IDNLearn.com: Where your questions meet expert answers and community support. Find reliable solutions to your questions quickly and accurately with help from our dedicated community of experts.
Sagot :
Answer:
(-12, -2)
Step-by-step explanation:
Rearrange the equation --> x^2 + 14x + 24 = 0
Split 14x into 12x + 2x --> x^2 + 12x + 2x + 24 = 0
Group --> x(x + 12) + 2(x + 12) = 0, (x + 12)(x + 2) = 0
Find roots:
x + 12 = 0, x = -12
x + 2 = 0, x = -2
The solution of the given expression [tex]\rm x^{2} +14x = -24\\[/tex] by completing the square method is 12 and -2.
The given expression is
[tex]\rm x^{2} +14x = -24\\[/tex]
What is completing the square method?
In completing the square, we take half of the coefficient of the middle term and then square it. Then we add it to both sides of the equation
Here coefficient of middle term x is +14.
So, 14/2 = 7
square of 7 is 49
[tex]\rm x^{2} +14x +49= -24+49\\\rm (x+7) (x+7)=25\\\rm (x+7)^{2} =5^{2} \\\rm x+7 =5[/tex]
x+7 = 5 and x+7 = -5
Solve for x by subtracting 7 on both sides
x = -2 and x= -12
Solution set is {-12, -2}
Learn more about completing the square;
https://brainly.com/question/4822356
We appreciate your contributions to this forum. Don't forget to check back for the latest answers. Keep asking, answering, and sharing useful information. Find clear answers at IDNLearn.com. Thanks for stopping by, and come back for more reliable solutions.